2005
DOI: 10.1177/1077558705275416
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Medical Interpreter Services on the Quality of Health Care: A Systematic Review

Abstract: Twenty-one million Americans are limited in English proficiency (LEP), but little is known about the effect of medical interpreter services on health care quality. Asystematic literature review was conducted on the impact of interpreter services on quality of care. Five database searches yielded 2,640 citations and a final database of 36 articles, after applying exclusion criteria. Multiple studies document that quality of care is compromised when LEP patients need but do not get interpreters. LEP patients' qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
824
2
28

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,096 publications
(923 citation statements)
references
References 40 publications
(67 reference statements)
26
824
2
28
Order By: Relevance
“…On the one hand culture-related communication differences were identified as hampering for mental health diagnoses, on the other hand there is a lack of mental health care options available targeted especially to refugees [15,16]. The results of this research are consistent to earlier studies [18–20]. …”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the one hand culture-related communication differences were identified as hampering for mental health diagnoses, on the other hand there is a lack of mental health care options available targeted especially to refugees [15,16]. The results of this research are consistent to earlier studies [18–20]. …”
Section: Introductionsupporting
confidence: 87%
“…Research has shown that PHC professionals and refugees or other migrants face equally great challenges when it comes to PHC encounters during the flight, upon and after arrival in the destination countries [15,16,18–20]. In response to these challenges, an online course/CME course for PHC professionals was developed, offering comprehensive knowledge on the issues of refugees’ and other migrants’ health to participants from different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to all prior inpatient studies we found a low use of interpreters by hospital clinicians. 5,6,21 Federal law, the Institute of Medicine (IOM), and hospital guidelines, including the Joint Commission standards, all recommend the routine use of professional interpreters during clinical encounters. 3,[22][23][24] It is possible that our low rate of interpreter use is due to the use of nonprofessional interpreters (i.e., family members or friends) and/or clinical encounters with bilingual physicians or other clinical staff and/or even LEP patients relying on their own limited English language abilities.…”
Section: Mutltivariable Analyses Of Hospital Outcomesmentioning
confidence: 99%
“…3,4 The use of professional medical interpreters is associated with increased patient satisfaction, quality of care, and improved disease-specific process measures and outcomes. 5,6 The Institute of Medicine report Crossing the Quality Chasm states that the use of an interpreter is not only a quality, but also a patient safety imperative. [7][8][9][10] Most studies to date have focused on the impact of interpreters in the outpatient and emergency department (ED) settings.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure equity, our healthcare system needs to effectively incorporate evidence‐based practices that facilitate quality care across language differences 5. Engaging professional medical interpreters (PMIs) in the care of patients with language barriers can help decrease clinical errors, enhance service utilization, improve clinical outcomes, and increase patient satisfaction 6. The role of PMIs in the care of stroke patients is largely unknown; we are aware of only 1 Australian study that showed patients undergoing inpatient stroke rehabilitation who needed and received PMI services had a greater change in their functional independence rate compared with patients who needed but did not receive PMI services 7.…”
mentioning
confidence: 99%